Myocarditis Following COVID-19 Vaccine Use: Can It Play a Role for Conditioning Immunization Schedules? - Esposito, Susanna; Caminiti, Caterina; Giordano, Rosanna; Argentiero, Alberto; Ramundo, Greta; Principi, Nicola (Frontiers in Immunology, 2022)
Myocarditis (MYO) is a relatively uncommon inflammatory disease that involves the heart muscle. It can be a very severe disease as it can lead to the development of acute or chronic heart failure and, in a not marginal number of cases, to death. Most of the cases are diagnosed in healthy people younger than 30 years of age. Moreover, males are affected about twice as much as females. Viruses are among the most common causes of MYO, but how viral infection can lead to MYO development is not precisely defined. After COVID-19 pandemic declaration, incidence rate of MYO has significantly increased worldwide because of the SARS-CoV-2 infection. After the introduction of anti-COVID-19 vaccines, reports of post-immunization MYO have emerged, suggesting that a further cause of MYO together with the SARS-CoV-2 infection could increase the risk of heart damage during pandemic. Main aim of this study is to discuss present knowledge regarding etiopathogenesis and clinical findings of MYO associated with COVID-19 vaccine administration and whether the risk of this adverse events can modify the initially suggested recommendation for the use of COVID-19 vaccines in pediatric age. Literature analysis showed that MYO is an adverse event that can follow the COVID-19 immunization with mRNA vaccines in few persons, particularly young adults, adolescents, and older children. It is generally a mild disease that should not modify the present recommendations for immunization with the authorized COVID-19 mRNA vaccines. Despite this, further studies are needed to evaluate presently undefined aspects of MYO development after COVID-19 vaccine administration and reduce the risk of development of this kind of vaccine complication. Together with a better definition of the true incidence of MYO and the exact role of the various factors in conditioning incidence variations, it is essential to establish long-term evolution of acute COVID-19 related MYO.